Retificador boost trifásico isolado com MPPT para geradores eólicos de pequeno porte - Pontes, Jhonatan de Abreu Soares (2022)
This work presents the development and implementation of a single-stage isolated three-phase boost rectifier with maximum power point tracking for applications in small wind turbines. The PFC structure can be seen as an association of two boost rectifiers with 4 switches and a midpoint operating in parallel in continuous conduction mode. It also provides high voltage gain, very interesting for small wind turbines since they have low voltage at their terminals. The Cphase inductor is suppressed causing a decrease in the amount of magnetic and consequently reducing value, weight and volume. Furthermore, the fact that phase C is connected at the midpoint reduces the effects of common mode current. The complete structure has two outputs each isolated by a high frequency transformer, making it possible for the structure to associate the output according to the desired application. The control of the structure has a fast current loop and a much slower one for the voltage bus, it also uses a balance loop that guarantees the balance of voltages in the capacitors of the main bus. The energy transfer between primary and secondary is guaranteed through phase shift modulation with a fixed angle . The structure operates with a switching frequency of 43.2 kHz and a rated power of 2 kW, with a maximum efficiency of 93.63 % for the PFC and 89 % for the isolated structure at approximately 1700 W.